Solve for x:

4(3x+7)=7

### 12 Answers | Add Yours

im not sure how your teacher asked you to solve the equations, but theres simple steps to follow to figure out for x;

- you want to get rid of the brackets, to do this multiply the numbers in brackets by 4
- rewrite the question, it should now be 12x + 28 =7
- now you want to isolate x, to do this subtract 28 from both sides of the equation
- rewrite the equation once again, it should now be 12x = -21
- now divide both sides of the equation by 12
- rewrite the equation one more time and you have your answer. x= -1.75
- dont forget to check your answer! :)

4(3x+7)=7

(3x+7)=7/4 divide both sides by 4

3x = 7/4 - 7 subtract 7 from both sides

x = (7/4 - 7)/3 divide both sides by 3

x = 7/12 -7/3 expand the parenthesis

x = 7/12 - 28/12 find common denominator (* by 4/4)

x = -21/12 subtract

**x = -7/4** simplify

4(3x+7)=7.

To solve for x, multiply by 4 to each of the terms inside the bracket in the left side:4*3x=12x. 4*-7=-28. The right side is retained as it is:

12x+28=7.

Subtract 28 from both sides to retain the unknown term 12x on the left and the known term or the numbers on the right:

12x+28-28=7-28.

Now 28-28 on the left cancel out.On the right 7-28= -21:

12x=-21.

Divide both sides by 12. On the left **12x/12 becomes x**.On the right -21/12, which is reduced to **-7/4** in the lowest equivalent fraction form.

Therefore, **x=-7/4 .**

Convert 7/4 in decimal form and attach the minus line at last.

7/4=1+3/4 =1.75.

Therefore,**x=-1.75 is our solution.**

Tally:

Put the solution, x=-1.75 in the original equation and see whether the equation is satisfied, in the sense the value on the left becomes equal to the right.

Left side :4*[3(-1.75)+7]=4*3(-1.75)+4*7=4*-5.25+28=-21+28=7.

Right side:7

Both sides are equal in value after putting x=-1.75. So the solution is verified.

4(3x+7)=7

12x+28=7

12x+28-28=7-28

12x=-21

12x/12=-21/12

x=-1.75

**4(3x+7)=7 ======>multiply 4 by 3x , 7**

**12x + 28 = 7 ========> add -28 both side**

**12x + 28 -28 = 7-28**

**12x = -21 =======> divid both side by 12**

**x = -21/12 = 1.75**

4(3x + 7) = 7

1) You can't do anything until you get rid of the parentheses. Use distributive property to get rid of those.

**12x + 28 = 7**

2) Now do the order of operations backwards. The first thing (going backwards) is addition/subtraction. What do you have in *your problem*? You have addition. The opposite of addition is subtraction.

**12x + 28 = 7**

** -28 -28**

**12x = -21**

3. Now you have 12x = -21. What operation is being used in the equation? Multiplication is. The opposite of multiplication is division. Now divide both sides by 12.

**12x = -21**

**x = -1.75**

4(3x+7)=7

4-3=1 1x7=7

4(3x+7)=7

you have to get rid of the parenthesis

distribute the 4 within the parentheis

12x+28=7

subtract 28 from both sides

12x+28=7

-28 -28

12x=-21

divide by 12

12x=-21

/12 /12

x=-1.75

4(3x+7)=7

* distribute the 4

- (4 * 3x)= 12x
- (4 * 7) = 28

12x + 28 = 7

- subtract 28 in both sides
- +28 -28 = 0
- 7 - 28 = -21

12x = -21

- Divide 12 to both sides to get the x alone
- (12x / 12 ) = x
- (-21/12) = -1.75

**x = -1.75**

4(3x+7)=7

12x+28=7

12x+28-28=7-28

12x=-21

12x/12=-21/12

x=-1.75

4(3x+7)=7

Divide both sides by 4

3x + 7 = 7/4

subtract 7

3x = (7/4) - 7

divide by 3

((7/4) - 7)/3

= -1.75

4(3x+7)=7

**x = -1.75**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes